Implicit and Explicit Taxes: Study of Asia Pacific Banking - Etika Karyani; Dwi Martani (The Indonesian Journal of Accounting Research, 2014)
Abstract: Reserve requirements act as an implicit tax on the banking industry that can affect their performance. Using bank-level data for 250 firm-years in the Asia Pacific region during the period 2007-2012 and panel data model through fixed effect regression with robust function, this paper analyzes how tax policy, bank characteristics, and macroeconomic environment affect the bank profitability. This study controls for the firm characteristics such as bank size, bank liquidity, and overhead, while the GDP variable to control the country characteristic. This paper confirms some of the findings in the previous studies that the implicit tax policy (reserve requirements) has a positive effect on bank profitability that is proxied with return on assets. While the explicit tax policy does not affect it. This study also gives evidence that the role of foreign bank ownership structure of both the reserve requirements and the explicit tax is higher than the foreign non-banks.Abstrak: Persyaratan cadangan bertindak sebagai pajak implisit pada industri perbankan yang dapat mempengaruhi kinerja mereka. Dengan menggunakan data tingkat bank selama 250 tahun perusahaan di kawasan Asia Pasifik selama periode 2007-2012 dan model data panel melalui regresi efek tetap dengan fungsi yang kuat, makalah ini menganalisis bagaimana kebijakan pajak, karakteristik bank, dan lingkungan makroekonomi mempengaruhi profitabilitas bank . Penelitian ini mengontrol untuk karakteristik perusahaan seperti ukuran bank, likuiditas bank, dan overhead, sedangkan variabel PDB untuk mengendalikan karakteristik negara. Makalah ini menegaskan beberapa temuan dalam studi sebelumnya bahwa kebijakan pajak implisit (persyaratan cadangan) memiliki efek positif pada profitabilitas bank yang diproksi dengan laba atas aset. Sementara kebijakan pajak eksplisit tidak mempengaruhinya. Penelitian ini juga memberikan bukti bahwa peran struktur kepemilikan bank asing baik dari persyaratan cadangan dan pajak eksplisit lebih tinggi dari non-bank asing.